Food and feeding habit of Gudusia chapra (Hamilton) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Food; feeding habit; electivity; Gudusia chapra Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 41-44